Design of Jigs, Fixtures and Press Tools - Venkataraman, K.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This textbook is aimed at providing the introductory knowledge on the subject to the undergraduate students studying mechanical and manufacturing engineering at most universities. Many of the universities prescribe a syllabus that contains both Design of Jigs and Fixtures, and Design of Press Tools in a single semester course. Keeping the above in mind, this book is designed in two parts. Part-I deals with Jigs and Fixtures and Part-II is earmarked exclusively for the study of Press Tools. Both these subjects are built progressively in successive chapters. A separate appendix, in each part, provides short answer questions with answers, which will help the students in clarifying doubts and strengthen their knowledge base. The explanatory notes and illustrations provided in the book will serve the purpose of awakening the interest of the students. End of chapter questions and answers aid to the learning process of students. This textbook will be extremely useful for the students and practicing engineers studying mechanical, manufacturing, and production engineering.
Introduction to Jigs and Fixtures -- Design of Locators -- Design of Clamps -- Drilling Jigs -- Design of Milling Fixtures -- Other Types of Fixtures.
Keywords: Manufactures; Machinery; Industrial engineering; Production engineering; Machines, Tools, Processes; Machinery and Machine Elements; Industrial and Production Engineering; Dies (Metal-working) -- Design and construction; Jigs and fixtures -- Design and construction; Machine-tools -- Design and construction